Georgia : Report on Observance of Standards and Codes: Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses the Report on the Observance of Standards and Codes (ROSC) on Data Module for Georgia. Following the 2002 ROSC mission, Georgia has continued to make impressive improvements in statistical compilation and dissemination in all areas of statistics covered by the Data ROSC. Georgia's macroeconomic statistics are generally of high quality and adequately meet users' needs. Georgia has made tangible improvements on the legal, institutional, methodological, and dissemination aspects of data quality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet